CROWDFUNDING FOR DEVELOPING WAQF LAND A STUDY ON MALAYSIA - Hapsari, Meri Indri; Bin, Mohamed Asmy; Muhammad, Mustafa Omar; Dausa, Jarita (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2020)
This present study aims to develop an alternative model of financing that address theproblems of waqf land financing in Malaysia, analyse the probability that waqf institutionwill use the proposed model and recommend policies to enhance the optimisation ofcrowdfunding for developing waqf land. This study focuses on potential donors in the fourstates in Malaysia, namely Pahang, Pulau Pinang, Selangor and Johor since these areas havesignificant waqf lands. The analysis is conducted using statistical analysis and logisticregression analysis. The study finds that there is a high probability of donors willing to usethe proposed model (CWM), particularly among non-married donors, females, low-middleincome donors, and those with more awareness of crowdfunding and waqf.